2019
DOI: 10.1136/jisakos-2018-000269
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic debridement has lower re-operation rates than arthrotomy in the treatment of acute septic arthritis of the knee: a meta-analysis

Abstract: ImportanceSeptic arthritis of the native knee joint is the most common bacterial joint infection. The management involves prompt surgical debridement and joint irrigation by arthroscopy or arthrotomy. This is the first systematic review and meta-analysis to compare arthroscopic debridement with arthrotomy for septic arthritis of native knee joint.ObjectiveThe purpose of this systematic review and meta-analysis is to compare re-operation rates, length of inpatient hospital stay (LOS) and functional outcome betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(92 reference statements)
2
12
0
Order By: Relevance
“…A similar meta-analysis evaluated arthroscopic and arthrotomy interventions in patients with septic arthritis of the knee. Seven studies with 1089 knees, in which 723 were treated with arthroscopy and 366 were treated with arthrotomy were analyzed, reporting a lower re-operation rate in patients treated with arthroscopy, while parameters such as length of hospital stay and functionality were not conclusive [33]. Unlike Panjwani et al [33], we included studies reporting the interventions of interest in other joints (shoulder, hip, wrist), finding similar results in the re-operation rate in favour of arthroscopy with a shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar meta-analysis evaluated arthroscopic and arthrotomy interventions in patients with septic arthritis of the knee. Seven studies with 1089 knees, in which 723 were treated with arthroscopy and 366 were treated with arthrotomy were analyzed, reporting a lower re-operation rate in patients treated with arthroscopy, while parameters such as length of hospital stay and functionality were not conclusive [33]. Unlike Panjwani et al [33], we included studies reporting the interventions of interest in other joints (shoulder, hip, wrist), finding similar results in the re-operation rate in favour of arthroscopy with a shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic debridement of a septic joint has the advantages of providing debridement of necrosis synovial tissue, irrigation of purulent enzymatically active material, and assessment of the joint with a minimum of operative morbidity [36]. Additionally, the arthroscopic procedure has been related to better joint functionality [33]. However, we were not able to evaluate this issue since the majority of the included studies did not report or evaluate the range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Panjawani et al 1 conducted a systematic review and meta-analysis to compare outcomes between arthroscopy and arthrotomy of septic native knees. 1 Seven studies were included, comprising 723 patients who underwent arthroscopic irrigation and debridement (I&D) and 366 patients who underwent open I&D. The relative risk of reoperation was significantly lower in the arthroscopy group, whereas the length of stay was lower in the arthroscopy group in all included studies, and one study reported better functional outcomes with arthroscopy. Furthermore, in a retrospective study of 1 50% in the arthroscopic I&D group required repeated irrigation should be listed as source 2.…”
mentioning
confidence: 99%
“…1 Seven studies were included, comprising 723 patients who underwent arthroscopic irrigation and debridement (I&D) and 366 patients who underwent open I&D. The relative risk of reoperation was significantly lower in the arthroscopy group, whereas the length of stay was lower in the arthroscopy group in all included studies, and one study reported better functional outcomes with arthroscopy. Furthermore, in a retrospective study of 1 50% in the arthroscopic I&D group required repeated irrigation should be listed as source 2. In addition, the arthroscopic group underwent a lower total number of irrigation procedures and had better mean postoperative range of motion (P < .05).…”
mentioning
confidence: 99%
“…Panjwani et al 1 conducted a systematic review and meta-analysis to compare reoperation rates, length of stay, and functional outcome between arthroscopy and arthrotomy in septic native knees. They found 7 studies comprising 723 patients who underwent arthroscopic irrigation and debridement (I&D) and 366 who underwent open I&D. The relative risk of reoperation was significantly lower in the arthroscopy group, the length of stay was lower in the arthroscopy group in all included studies, and 1 study reported better functional outcomes with arthroscopy.…”
mentioning
confidence: 99%